Ketahanan Bersekolah Anak Miskin Usia 10-18 Tahun di Provinsi Nusa Tenggara Timur Tahun 2021 - Tanzil, Kevin Leonard Christian; Ekaria, Ekaria (Seminar Nasional Official Statistics, 2023)
Learning outcomes in several Indonesian provinces remain notably low, evident by high school dropout rates, including in East Nusa Tenggara Province. Children from impoverished households face a greater risk of school discontinuation. In 2021, East Nusa Tenggara Province ranked as the third highest in poverty-stricken population and had the largest school-age population percentage in Indonesia. This study aims to provide a general overview of internal and external factors influencing school dropout among impoverished individuals aged 10-18 in East Nusa Tenggara Province in 2021, along with associated variables. The research employs 2021 National Socio-Economic Survey data and a livelihood analysis using the accelerated failure time model. The study reveals that variables such as employment status, household head's education, parental completeness, and participation in the Indonesia Pintar Program affect school attendance resilience, with a notable impact from the child's employment status on rapid school discontinuation.